Phytoplankton diversity in a tropical bay, North Borneo, Malaysia as revealed by light microscopy and Next-Generation Sequencing - Chong, Brian Wei Khong; Leong, Sandric Chee Yew; Victor S. Kuwahara; Teruaki Yoshida (Springer Nature, 2022)
Assessments of phytoplankton diversity in Sabah waters, North Borneo, have primarily relied on morphologybased identification, which has inherent biases and can be time-consuming. Next-Generation Sequencing (NGS) technology has been shown to be capable of overcoming several limitations of morphology-based methods. Samples were collected from the Sepanggar Bay over the course of the year 2018 in different monsoon seasons. Morphology-based identification and NGS sequencing of the V8–V9 region of the 18S LSU rDNA were used to investigate the diversity of the phytoplankton community. Microscopy and NGS showed complementary results with more diatom taxa detected by microscopy whereas NGS detected smaller and rarer taxa. The harmful algal genera in the study site comprised of Skeletonema, Margalefidinium, Pyrodinium, Takayama, and Alexandrium as detected by NGS. This study showed that that an integrative approach of both morphological and molecular techniques could provide more comprehensive information about the phytoplankton community as the approach captured quantitative variability as well as the diversity of phytoplankton species.